Konseling Keluarga Berencana Menggunakan Alat Bantu Pengambilan Keputusan (ABPK) terhadap Pengetahuan dan Sikap Ibu Nifas tentang Alat Kontrasepsi - Ermalina Ermalina; Rifa Yanti; Fajar Sari Tanberika; Dilgu Meri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of family planning counseling using a Decision-Making Aid (DMA) on postpartum women's knowledge and attitudes about contraception at the Sei Lala Community Health Center (UPT) in Indragiri Hulu Regency. The method used was a quantitative study with a quasi-experimental design using a one-group pretest-posttest. The results showed increases in knowledge and attitudes among postpartum women after receiving family planning counseling using the DMA, with p-values of 0.000 for knowledge and 0.014 for attitudes (p < 0.05). This study concludes that family planning counseling using a Decision-Making Aid (DMA) significantly increased postpartum women's knowledge and attitudes about contraception at the Sei Lala Community Health Center (UPT) in Indragiri Hulu Regency. Keywords: Decision-Making Aid, Postpartum Women, Family Planning Counseling, Knowledge, Attitude